SORPTION ISOTHERMS FOR FOOD PRODUCTS: STUDY OF MODELS AGREEMENT - NASCIMENTO, FABIANO RIBEIRO; CÔRREA, JEFFERSON LUIZ GOMES; BORGES, SORAIA VILELA; TOSATO, POLIANA GASPAR (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2011)
The knowledge of sorption isotherms is important for establishing conditions of storage and of processes like drying. There are several models for fitting sorption isotherms. This work presents a study about the agreement of 40 mathematical models of sorption isotherms to experimental data of 53 food products. The quadratic residual sum and the standard error were the criteria of evaluation. For the major part of the products, the best agreement was obtained with equation of Jaafar and Michalowski, if temperature or saturation pressure were not considered as a variable. For cases where temperature or saturation pressure were considered, the equation of Strohman and Yoerger was the one with the best agreement for most of the products. Ross equation, based on thermodynamics aspects, was also tested for some products, but the agreement was just satisfactory.